The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s00392-014-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bosentan therapy on ventricular and atrial function in adults with Eisenmenger syndrome. A prospective, multicenter study using conventional and Speckle tracking echocardiography

Abstract: In adult patients with Eisenmenger syndrome, bosentan therapy improves ventricular and atrial functions resulting in enhancement of physical exercise and reduction in the NT-proBNP level, while the pulmonary vascular resistance does not change substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…4 Bosentan is an orally active, selective and competitive non-peptide dual endothelin receptor (both ET A and ET B ) antagonist and usually used in cure of PAH. 5 Bosentan is also being considered for treatment of other conditions such as Eisenmenger syndrome, 6 persistent pulmonary hypertension of the newborn, 7 digital ulcer prevention in patients with systemic sclerosis, 8 adolescent and adult patients who have undergone Fontan operation, 9 vascular remodeling and dysfunctional angiogenesis in diabetes 10 and possibly even depression. 11 For treatment of PAH, bosetan is currently administered at the daily dose of 125-250 mg. 12 The maximum plasma peak is seen within 3-5 h after oral intake and the half-life of drug is 5.4 h. 13 Moreover, the bioavailability of bosentan after oral administration is approximately low (50%) 14 and variability is seen in bosentan absorption which may get back to its poor water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…4 Bosentan is an orally active, selective and competitive non-peptide dual endothelin receptor (both ET A and ET B ) antagonist and usually used in cure of PAH. 5 Bosentan is also being considered for treatment of other conditions such as Eisenmenger syndrome, 6 persistent pulmonary hypertension of the newborn, 7 digital ulcer prevention in patients with systemic sclerosis, 8 adolescent and adult patients who have undergone Fontan operation, 9 vascular remodeling and dysfunctional angiogenesis in diabetes 10 and possibly even depression. 11 For treatment of PAH, bosetan is currently administered at the daily dose of 125-250 mg. 12 The maximum plasma peak is seen within 3-5 h after oral intake and the half-life of drug is 5.4 h. 13 Moreover, the bioavailability of bosentan after oral administration is approximately low (50%) 14 and variability is seen in bosentan absorption which may get back to its poor water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with advanced therapies [17,18,19] for a su cient period to assess the hemodynamic and symptomatic response is strongly recommended before closure [13,14] .Supomo et al [20] described a ASD-ES female with highly symptomatic PAH(NYHA class III, mPAP 77 mmHg, PVR 4 Wood U) underwent occlusion successfully after oral beraprost for two years. After surgery her mPAP decrease to 38 mmHg with PVR of 2.52 Wood U. Hu et al [21] reported a ventricular septal defect (VSD)-ES patient with initial PVR of 18.84 Wood U underwent a successful operation after oral bosentan for 12 weeks, as a result of which her PVR decreased to 9.63 Wood U.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with advanced therapies [17,18,19] for a su cient period to assess the hemodynamic and symptomatic response is strongly recommended before closure [13,14] .Supomo et al [20] described a atrial septal defect(ASD)-ES female with highly symptomatic PAH(NYHA class III, mean PAP 77 mmHg, PVR 4 Wood U) underwent occlusion successfully after oral beraprost for two years. After surgery her mean PAP decrease to 38 mmHg with PVR of 2.52 Wood U. Hu et al [21] reported a ventricular septal defect (VSD)-ES patient with initial PVR of 18.84 Wood U underwent a successful operation after oral bosentan for 12 weeks, as a result of which her PVR decreased to 9.63 Wood U.…”
Section: Discussionmentioning
confidence: 99%